The Effectiveness of a Positive Psychology–Based Intervention in Reducing Maladaptive Perfectionism and Enhancing Quality of Life Among Physicians with OCPD Traits - Mohammadi, Mohammad Hosein; Almasi , Reza; Peighambar Zadeh, Azamossadat; Jafari Dehnayebi , Maedeh (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study evaluated the effectiveness of a positive psychology–based intervention in reducing maladaptive perfectionism and enhancing quality of life among physicians with OCPD traits in Tehran, Iran. Methods and Materials: Sixty physicians meeting criteria for OCPD traits (via SCID-5-PD) were randomly assigned to either an intervention group (n = 30) that received an 8-week group-based positive psychology program or a waitlist control group (n = 30). Measures included the Frost Multidimensional Perfectionism Scale (FMPS) maladaptive subscales and the WHOQOL-BREF, administered at baseline, post-intervention, and three-month follow-up. Repeated-measures ANOVA and Jacobson–Truax clinical significance criteria were applied. Findings: Repeated-measures ANOVA revealed significant group × time interactions for both maladaptive perfectionism (F(2, 116) = 36.09, p < .001, η² = .38) and quality of life (F(2, 116) = 31.62, p < .001, η² = .35). The intervention group demonstrated large effect size improvements (Cohen’s d = 1.57 for perfectionism; d = 1.88 for quality of life), which were maintained at follow-up. Clinically significant improvement was observed in 70% of participants for perfectionism and 67% for quality of life in the intervention group, compared to 10% and 7% in the control group, respectively (χ² values = 22.50 and 23.25, p < .001). Conclusion: Findings provide strong evidence that positive psychology interventions can effectively reduce maladaptive perfectionism and improve quality of life in physicians with OCPD traits. These results highlight the potential of integrating structured positive psychology programs into physician wellness initiatives to reduce burnout risk and enhance overall functioning.